The Streets of Laredo - Frank Maynard (Symphony in the Flint Hills, 2014)
One of the best-known of the old cowboy folksongs has a Butler County connection. In his memoir of his days as an open-range cowboy throughout the 1870s, Frank Maynard, whose home was Towanda in the western edge of the Flint Hills, told how he came to write the lyrics to the song we know as “The Cowboy’s Lament” or “The Streets of Laredo,” which he set at the doorway of Tom Sherman’s barroom in Dodge City.
Keywords: folksong; folk; music; musician; composition; cowboy; trail; Laredo; Kansas; Dodge City; The Dying Cowboy; song; tune; Chorus